Exploitation Assessment of New Holland CX780 Combine Harvester (Agricultural Engineering, 2016)
The article presents an exploitation assessment of New Holland CX780 combine operation. Significant technical and technological progress is visible in modern harvesters. Inter alia, performance increased and elements improving the quality of work of harvesters appeared. The objective of the paper was to determine efficiency of the New Holland CX780 harvester operation including factors which affect its operation. Time structures of particular activities of combine operation and ratios of these times use were determined during tests. Yield value and moisture of collected seeds was determined. Studies proved that effective time of combine operation in the process of rapeseed and wheat grain harvesting was less than 50% and was caused by long preparation of a machine for operation. Preparation for operation of a combine influences its performance in the total time. It was 22% of the total operation time in case of wheat harvesting and 20% in case of rapeseed harvesting.